2016
DOI: 10.1097/md.0000000000002778
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Resistance is Associated With Total Bile Acid Level in Type 2 Diabetic and Nondiabetic Population

Abstract: Bile acid metabolism was reported to be involved in glucose metabolism homeostasis. However, the exact relationship between bile acid and glucose metabolism as well as insulin sensitivity is not clarified. Therefore, we sought to investigate the association between insulin sensitivity and hyperbileacidemia in type 2 diabetic and nondiabetic population.This community-based cross-sectional study included 9603 residents from Jiading, Shanghai, China, who were 40 years and older. Standardized questionnaire, anthro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 31 publications
1
35
1
1
Order By: Relevance
“…Mechanistic studies in insulin-resistant mice suggest that impaired insulin-mediated repression of FoxO1 results in higher 12α-hydroxylase CYP8B1 expression [17]. Moreover, insulin resistance was associated with increased total BA concentrations [18,19], fasting tauro-conjugated BAs [20], CDCA, CA, DCA [13] and GCDCA [21].…”
Section: Bile Acids In Obesity Insulin Resistance and Type 2 Diabetesmentioning
confidence: 99%
“…Mechanistic studies in insulin-resistant mice suggest that impaired insulin-mediated repression of FoxO1 results in higher 12α-hydroxylase CYP8B1 expression [17]. Moreover, insulin resistance was associated with increased total BA concentrations [18,19], fasting tauro-conjugated BAs [20], CDCA, CA, DCA [13] and GCDCA [21].…”
Section: Bile Acids In Obesity Insulin Resistance and Type 2 Diabetesmentioning
confidence: 99%
“…It is clear from the literature that there are fundamental differences in bile acid metabolism regulated by total body adiposity between lean and obese individuals independent of insulin resistance. Several groups have shown decreased circulating concentrations of bile acids in obesity relative to leans (Albaugh et al, 2015; Cariou et al, 2011), though others suggest that insulin resistance drives increased bile acid synthesis and circulating bile acids (Haeusler et al, 2015; Sun et al, 2016). In addition to increasing synthesis and pool size, insulin resistance is associated with altered bile acid composition, specifically increased abundance of 12α-hydroxylated bile acid species which may be important negative regulators of insulin action (Haeusler et al, 2013).…”
Section: Bile Acids and Obesitymentioning
confidence: 99%
“…Alterations in total BA have been shown in subjects with prediabetes, T2DM, and IR [41]. In a cross-sectional study that included 9603 subjects, Sun et al [42] showed an increase of BA in IR individuals regardless of the presence/absence of T2DM, and they pointed out the important role of IR in BA metabolism regulation. However, noteworthily, the study enrolled subjects that were not severely obese.…”
Section: Discussionmentioning
confidence: 99%